FACTORS INFLUENCING E-WALLET USAGE OF GEN Z COLLEGE STUDENTS IN PURCHASING FASHION ITEMS: THE MEDIATING ROLE OF BEHAVIORAL INTENTION - Bonotan IV, Manuel Alexander C.; Cesa, Hernando Antonio A.; Dugenia, Francis Amiel L.; Marin, Martin Andrew C; Etrata, Antonio (Management Department, Faculty of Economics and Business, Universitas Jambi, 2026)
This study investigates the factors influencing Generation Z college students' adoption of e-wallets for purchasing fashion items in Manila-based colleges. With the rapid rise of digital payment systems and the growth of e-commerce in the fashion industry, understanding the variables that affect e-wallet adoption among this demographic has become essential for both academic institutions and industry stakeholders. Using a quantitative research design, the study primarily employs descriptive correlational analysis and surveys for data collection, utilizing a 1-6 Likert scale, where 1 indicates the lowest agreement and 6 indicates the highest. Partial Least Squares Structural Equation Modelling (PLS-SEM) was applied to assess the relationships between the key constructs. The results highlight that Behavioral Intention is a critical determinant in the adoption of e-wallets among Generation Z students, especially for purchasing fashion items. Moreover, Perceived Ease of Use, Perceived Usefulness, and Perceived Security were found to directly influence e-wallet usage, with these effects being significantly mediated by Behavioral Intention. This research provides important insights for both educators and industry stakeholders. For academic institutions, the findings suggest the need to incorporate digital payment education into curricula to foster a better understanding of emerging payment technologies. For fashion e-commerce businesses and payment providers, the study underscores the importance of enhancing Perceived Ease of Use, Perceived Usefulness, and Perceived Security to increase the adoption of e-wallets. Tailored marketing strategies that emphasize convenience, security, and utility could drive greater engagement with this tech-savvy demographic, ultimately improving user satisfaction and sales performance in the fashion sector.